ANALYSIS OF MUTATION AND WORKLOAD ON EMPLOYEE PRODUCTIVITY AT PANCA BUDI DEVELOPMENT UNIVERSITY WITH WORK MOTIVATION AS THE DRIVING FORCE INTERVENING VARIABLE - Rika Mustika Tarigan; Emi Wakhyuni; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2025)
This study was conducted to see how the effect of mutation and workload on employee productivity through motivation as an intervening variable in a case study at the University of Pembangunan Panca Budi Medan. The population in this study were employees at Universitas Pembangunan Panca Budi Medan who had the status of orientation, contract and permanent employees totalling 127 employees with a sample size of 56 people where the sample size was determined by the Slovin formula. The data used are primary data and secondary data taken directly from respondents using questionnaires and data from internal agencies. This type of research is associative quantitative. Data processing using Smart - PLS version 4.0 software with path analysis using Structural Equation Modeling (SEM-PLS) analysis techniques. The research results from hypothesis testing show that mutations directly have no effect on motivation as indicated by p values of 0.100> 0.05. Workload directly affects work motivation as shown by p values of 0.02 < 0.05. Mutation directly has no effect on employee productivity as shown by p values of 0.344 > 0.05. Workload directly has no effect on employee productivity which is shown in p values 0.190 > 0.05. Motivation directly affects employee productivity as shown in p values of 0.010 < 0.05. Mutation through motivation indirectly has no effect on employee productivity as shown in p values 0.161 > 0.05. Workload through motivation indirectly g has no effect on employee productivity shown in p values 0.083 > 0.05.